GALLIUM SPECIATION IN AQUEOUS SOLUTION. EXPERIMENTAL STUDY AND MODELLING: PART 1. THERMODYNAMIC PROPERTIES OF GA(OH)-4 TO 300°C - Diakonov I.I.; Pokrovski G.S.; Bénézeth P.; Schott J.; Dandurand J.L.; Escalier J. (My University, 1997)
The solubility of α-GaOOH was measured in low ionic strength (0.025 M) HClNaCl solutions over the pH range 1.6–4.1 at 150, 200, and 250°C. A least squares linear regression of these data was used to determine the dissociation constants (Ks0∗ to Ks3∗) of the mineral from which hydrolysiss constants of aqueous gallium species were derived. The dissociation constants generated in this study were used together with the thermodynamic properties of α-GaOOH (Pokrovski et al., 1997) to calculate the standard partial molal thermodynamic properties at 25°C, 1 bar and the equations of state parameters for Ga3+, Ga(OH)2+, Ga(OH)2+, and Ga(OH)30 within the framework of the revised HKF model (Tanger and Helgeson, 1988; Shock and Helgeson, 1988; Shock et al., 1992). These thermodynamic properties enabled calculation of gallium speciation as a function of pH and temperature. Our results indicate that the hydrolysis of Ga occurs at low pH and its speciation is strongly dominated by the negatively-charged species Ga(OH)4− in the pH range of natural solutions at 25°C. At increasing temperature, the amount of Ga(OH)2+ and Ga(OH)30 becomes significant. These data are used to compare the geochemical behavior of Ga and Al in natural fluids.